What is happening with Political Philosophy? - Hernando Nieto, Eduardo (2025)
From a critical perspective on the development of contemporary political science, this article seeks to highlight the practical advantages provided by theoretical political knowledge, not only for conceptual clarification but also for understanding political dynamics and their projections. Precisely, the fact that current approaches to local political science prioritize qualitative and quantitative research, leaving out the contributions to political knowledge that subjects such as political philosophy or the history of political ideas can provide—except to include them within theoretical frameworks alone—would ultimately weaken the growth and robustness of the discipline.